The Impact of Synchronicity on Block Trading: Moderating Role of Media Coverage - Mehrab Nasiry; Hossien Fakhari; Esfandiar Malekian (راهبرد مدیریت مالی)
Block trading is used by investors in the capital market because it provides company-specific information, which is a tool for optimal stock pricing. Additionally, the media can bring the interests of managers and shareholders closer together by publishing company-specific news, thereby reducing information asymmetry, increasing stock price awareness, and decreasing stock price coincidence. Therefore, the purpose of this study is to investigate the moderating role of media coverage in the effect of block trading on stock price synchronicity. The statistical population of this research consists of companies listed on the Tehran Stock Exchange from 1393 to 1401, which were selected through systematic deletion of data from 100 companies, including 11,237 block transactions for review, experience, and analysis. The results of the Multivariate regression model based on composite data showed that the number and block trading ratio have a positive effect on stock price synchrony. Moreover, media coverage as a moderator variable in the effect of block trading ratio has a negative effect on stock price synchrony. These findings emphasize the inefficiency and lack of transparency of information in the Iranian stock market, which prevents the timely incorporation of company-specific information into stock prices.